2014
DOI: 10.3171/2014.4.jns131198
|View full text |Cite
|
Sign up to set email alerts
|

STAT-1 expression is regulated by IGFBP-3 in malignant glioma cells and is a strong predictor of poor survival in patients with glioblastoma

Abstract: Object Insulin-like growth factor binding proteins (IGFBPs) have been implicated in the pathogenesis of glioma. In a previous study the authors demonstrated that IGFBP-3 is a novel glioblastoma biomarker associated with poor survival. Since signal transducer and activator of transcription 1 (STAT-1) has been shown to be regulated by IGFBP-3 during chondrogenesis and is a prosurvival and radioresistant molecule in different tumors, the aim in the present study was to explore the functional significance of IGFBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…7,18 A previous study showed that IGFBP3 knockdown impaired the proliferation capability of U-251 MG glioma cells in vitro. 24 Here, we performed IGFBP3 knockdown by expressing IGFBP3 siRNAs in five glioma cell lines and four GBM primary cell lines and confirmed a growth-suppressing effect of IGFBP3 depletion in vitro; we further suggested a tumor-growth suppression effect of IGFBP3 siRNAs in in vivo intracranial xenograft mouse models. Our findings demonstrate that depleting IGFBP3 expression by IGFBP3 siRNA is a novel and promising targeted therapy in treating GBM patients.…”
Section: Discussionsupporting
confidence: 60%
“…7,18 A previous study showed that IGFBP3 knockdown impaired the proliferation capability of U-251 MG glioma cells in vitro. 24 Here, we performed IGFBP3 knockdown by expressing IGFBP3 siRNAs in five glioma cell lines and four GBM primary cell lines and confirmed a growth-suppressing effect of IGFBP3 depletion in vitro; we further suggested a tumor-growth suppression effect of IGFBP3 siRNAs in in vivo intracranial xenograft mouse models. Our findings demonstrate that depleting IGFBP3 expression by IGFBP3 siRNA is a novel and promising targeted therapy in treating GBM patients.…”
Section: Discussionsupporting
confidence: 60%
“…Finally, the DNA/protein transcription factor interaction array experiment revealed that HEY1 binds a large number of transcription factors, including both STAT1 and STAT4. Although PCR data does not show si-HEY1 to have a significant effect on STAT1, previous research indicates the overexpression of STAT1 is unique to glioblastoma samples when compared to normal brain tissue samples [ 26 ]. More significantly, STAT1 levels have been correlated with shorter median survival time in patients with GBM (STAT1+ = 13 months; STAT1- = 21 months) [31].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that Pyk2 has a key role in the basic migratory activity of U87 and HS683, but not A172, GL261, and C6 cells. These might suggest that in addition to Pyk2 other pathways may be involved in the regulation of basal rates of migration in gliomas such as Insulin-like growth factor binding protein 3 (IGFBP-3) that has been implicated in the pathogenesis of gliomas and was shown to be involved in proliferation and the invasive capacity of glioma cells [ 53 ]. Other studies demonstrated that Culllin1 (Cul1) is increased significantly in malignant brain tumors, and that silencing of Cul1 in glioma cells inhibited the cell migration and invasion abilities as well as down-regulated MMP-2 and MMP-9 expression that also greatly contribute to the reduced cell invasion and migration abilities [ 54 ].…”
Section: Discussionmentioning
confidence: 99%